2018
DOI: 10.1021/acsenergylett.8b01909
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Near-Unity Photoluminescence Efficiency for Blue-Violet-Emitting Perovskite Nanocrystals

Abstract: While perovskite nanocrystals (NCs) have shown great promise as materials for efficient light-emitting diodes (LEDs), low photoluminescence quantum yield (PLQY) of the blue-emitting perovskites is an impediment to the development of white LEDs of which blue is an essential component. Herein, we report that room temperature postsynthetic treatment of weakly blue-violet-emitting (PLQY 3%) CsPbCl3 NCs with CdCl2 results in an instantaneous enhancement of the PLQY to near-unity without affecting the PL peak positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
359
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(370 citation statements)
references
References 46 publications
11
359
0
Order By: Relevance
“…Figure 4c displays the steady-state PL spectra of PbS-PbX 2 and PbS-AI QD solid film. [50,51] A slower PL decay was observed for PbS-AI QD solid film compared with that of PbS-PbX 2 QD solid film. The timeresolved PL decay measurement was performed using a timecorrelated single-photon counting (TCSPC) technique, which could directly detect the dynamic of photoinduced charge carrier in CQD solid.…”
Section: Charge Recombination and Collectionmentioning
confidence: 95%
“…Figure 4c displays the steady-state PL spectra of PbS-PbX 2 and PbS-AI QD solid film. [50,51] A slower PL decay was observed for PbS-AI QD solid film compared with that of PbS-PbX 2 QD solid film. The timeresolved PL decay measurement was performed using a timecorrelated single-photon counting (TCSPC) technique, which could directly detect the dynamic of photoinduced charge carrier in CQD solid.…”
Section: Charge Recombination and Collectionmentioning
confidence: 95%
“…Capping ligands are used to stabilize/solubilize nanocrystals in different solvents . Generally, primary amines are used as capping ligands during the synthesis of lead halide perovskite nanocrystals .…”
mentioning
confidence: 99%
“…Recently, PLQY values of 98% were described for blue‐violet–emitting CsPbCl 3 perovskite NCs, which were treated with CdCl 2 after the synthesis. This postsynthetic treatment of the perovskite NCs does not show any effect on the position of the photoluminescence (PL) peak and the spectral width . We found that OIHP semiconductor quantum wells thermodynamically prefer to form lamellar superlattices, which exhibit the AIE characteristics.…”
Section: Bright Luminescence and High Quantum Yields In Perovskite Ncsmentioning
confidence: 85%
“…As we discussed earlier, the PLQYs for semiconductor perovskite emitters are approaching nearly 100% in both solutions and solids . Apart from that, it is interesting to investigate the blue and red emissions in perovskites QDs.…”
Section: Development Of Rgb Perovskite Qdsmentioning
confidence: 90%
See 1 more Smart Citation